Betaine Reduces Lipid Anabolism and Promotes Lipid Transport in Mice Fed a High-Fat Diet by Influencing Intestinal Protein Expression - Haitao Hu; Lun Tan; Xiaojiao Li; Jingjing Li; Caiyun Fan; Feng Huang; Zhao Zhuo; Kun Hou; Yinying Xu; Qingfeng Wang; Yongxin Yang; Jianbo Cheng (Foods, 2022)
Betaine is more efficient than choline and methionine methyl donors, as it can increase nitrogen storage, promote fat mobilisation and fatty acid oxidation and change body fat content and distribution. Lipid is absorbed primarily in the small intestine after consumption, which is also the basis of lipid metabolism. This study was conducted to establish a mouse model of obesity in Kunming mice of the same age and similar body weight, and to assess the effect of betaine on the intestinal protein expression profile of mice using a proteomic approach. Analysis showed that betaine supplementation reversed the reduction in expression of proteins related to lipid metabolism and transport in the intestine of mice induced by a high-fat diet (HFD). For example, the addition of betaine resulted in a significant upregulation of microsomal triglyceride transfer protein (Mttp), apolipoprotein A-IV (Apoa4), fatty-acid-binding protein 1 (Fabp1) and fatty-acid-binding protein 2 (Fabp2) expression compared to the HFD group (p < 0.05), which exhibited accelerated lipid absorption and then translocation from the intestine into the body’s circulation, in addition to a significant increase in Acetyl-CoA acyltransferase (Acaa1a) protein expression, hastening lipid metabolism in the intestine (p < 0.05). Simultaneously, a significant reduction in protein expression of alpha-enolase 1 (Eno1) as the key enzyme for gluconeogenesis in mice in the betaine-supplemented group resulted in a reduction in lipid synthesis in the intestine (p < 0.05). These findings provide useful information for understanding the changes in the protein profile of the small intestine in response to betaine supplementation and the potential physiological regulation of diets’ nutrient absorption.